PENGARUH KOMPENSASI EKSEKUTIF, KARAKTER EKSEKUTIF, DAN KOMITE AUDIT TERHADAP AGRESIVITAS PAJAK - Lilis Kamilah (2022)
This study aims to examine and determine the effect of executive compensation, executive character, and audit committee on tax aggressiveness (Empirical Study on Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The population in this study were 193 listed manufacturing companies on the Indonesia Stock Exchange in 2018-2020, with a total sample of 47 companies. The sample selection technique used purposive sampling with quantitative methods using panel data. The data analysis used was multiple linear regression, using the STATA application version 16. The measurement used for aggressiveness tax, using two measurements, namely conforming tax avoidance and non-conforming tax avoidance. The results obtained are: executive character, executive compensation has a negative effect on tax aggressiveness with conforming tax avoidance, but the audit committee has no effect on tax aggressiveness with conforming tax avoidance. Executive compensation has a positive effect on tax aggressiveness with non-conforming tax avoidance, the audit committee has a negative effect on tax aggressiveness, but the executive character has no effect on tax aggressiveness with non-conforming tax avoidance.